Matemática como discurso - Skovsmose, Ole [UNESP] (My University, 2013)
Initial steps are taken towards an interpretation of the discourse of mathematics, by showing that a mathematical model does not represent, but re-present; that it is not objective, but that it invents its objects; and that it is not descriptive, but performative. Mathematics-based discursive acts become identified, as crucial elements in an interpretation of mathematics as discourse. The discursive acts are: (1) technological imagination, (2) hypothetical reasoning, (3) legitimation or justification, (4) realisation, and (5) dissolution of responsibility. Through such acts, mathematics exercises symbolic power and makes possible new forms of symbolic violence.
Mathematics as discourse
Keywords: Analytic duality-interpretation of language; Discursive acts; Discursive interpretation of language; Symbolic power; Symbolic violence